The Encyclopedia of colored pencil techniques - Martin, Judy frey50 (Philadelphia Running press, 1992)
Explains basic charactericstic and color ranges of the main kinds of colored pencils. Offers step-by-step demonstrations of each technique, and examples of professional artists' work